The unique development path of developing countries - Hoang Xuan Long; Hoang Lan Chi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2023)
The development efforts of developing countries often involve following paths that have been previously charted by more developed industrial nations. In practice, replicating historical trajectories has not always led to the anticipated successes. This article presents an analysis of the significance of a unique development path for developing countries, including its constituent elements, processes, and foundations. These fundamental aspects shed light on the feasibility and stringent conditions and the substantial challenges that developing countries must overcome on their individual development journeys. Code: 23022001